Stator flux in direct torque control using a speed and torque variation-based sector rotation approach - Siti Azura Ahmad Tarusan; Auzani Jidin; Mohd Luqman Mohd Jamil; Kasrul Abdul Karim (Institute of Advanced Engineering and Science, 2021)
A typical problem of traditional DTCs is that the stator flux fails to regulate at low running speeds. The regulation of stator flux in DTC is disrupted because of the unavoidable voltage drop across the stator resistance. As a result, one of the solutions to the problem is to use a fixed sector rotation technique. The concept is based on decreasing stator flux droop, a simple technique for changing the flux locus sector at a certain angle. This method, however, is only effective at low working speeds at one value of torque. As a result, the stator flux droop effect at various speeds as well as torque must be studied. The study is carried out in this paper using simulation (MATLAB/Simulink) and a practical setup (dSPACE board) where both have performed similar outcomes. The comparison is done between the conventional method (without a strategy) and the proposed method (with strategy). In summary, the effect of stator flux droop has been found to have an inverse linear relationship to the speed and torque variation.